2015
DOI: 10.3389/fphys.2015.00037
|View full text |Cite
|
Sign up to set email alerts
|

Fibrosis: a structural modulator of sinoatrial node physiology and dysfunction

Abstract: Heart rhythm is initialized and controlled by the Sinoatrial Node (SAN), the primary pacemaker of the heart. The SAN is a heterogeneous multi-compartment structure characterized by clusters of specialized cardiomyocytes enmeshed within strands of connective tissue or fibrosis. Intranodal fibrosis is emerging as an important modulator of structural and functional integrity of the SAN pacemaker complex. In adult human hearts, fatty tissue and fibrosis insulate the SAN from the hyperpolarizing effect of the surro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(87 citation statements)
references
References 100 publications
3
84
0
Order By: Relevance
“…Based on anatomic and functional data 4,5 , frozen SAN tissues (cryo blocks) were cut into head, center and tail blocks (~4-6 mm long), respectively perpendicular to epicardium (Figure 1). In keeping with previous studies 4, 17-19 , we describe the most superior third of the SAN as the ‘‘head’’, the middle third as the ‘‘center’’, and the inferior third as the ‘‘tail’’ (Figure 1A). Cryosections were collected from both ends of the cryo blocks at 20μm thickness.…”
Section: Methodssupporting
confidence: 71%
“…Based on anatomic and functional data 4,5 , frozen SAN tissues (cryo blocks) were cut into head, center and tail blocks (~4-6 mm long), respectively perpendicular to epicardium (Figure 1). In keeping with previous studies 4, 17-19 , we describe the most superior third of the SAN as the ‘‘head’’, the middle third as the ‘‘center’’, and the inferior third as the ‘‘tail’’ (Figure 1A). Cryosections were collected from both ends of the cryo blocks at 20μm thickness.…”
Section: Methodssupporting
confidence: 71%
“…3). Structural remodeling, which is characterized by fibrosis within the SAN, increases with aging in human and animal (such as the mouse) models [28,29]. However, histological sections (Masson trichrome stain) illustrated that fibrosis was not significantly increased with aging in the SANs of dogs [2.5% (young group) vs. 2.7% (adult group) vs. 2.3% (aged group)] in terms of the collagen volume fraction, while adipose tissue gradually increased in the SAN (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This process includes a decrease in the number of pacemaker cells and an increase in collagen content during aging [12]. Therefore, structural remodeling is considered to be the cause of the functional decline within the SANs of elderly animals [28]. However, the effect of structural remodeling in aged SANs remains controversial [11,15].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is associated with pathological myocardial changes such as myocyte hypertrophy, fibrosis, focal myocardial disarray, fatty infiltration, and increased epicardial fat [27]. The effect of myocardial fibrosis on sinus node function and the electrical conduction system has been described previously [28]. Thus, previous animal studies have shown that metabolic syndrome and obesity induce alterations of sinus node function due to fat accumulation around nodal cardiomyocytes and changes in sympathetic innervation [29,30].…”
Section: Obesity and Metabolic Syndromementioning
confidence: 99%